AIDS, fear, and society challenging the dreaded disease - Doka, Kenneth J. (Series in death education, aging, and health care, 1997)
This text examines the deep sense of fear that AIDS evokes, stigmatizing those who suffer from the disease, as well as their families and caregivers. Until AIDS can be seen for what it actually is - a life- threatening disease - policies providing for humane treatment will not evolve